Transportation planning and development in the eyes of Al-Quran and Al-Ahadith - Bachok, Syahriah (IIUM Press, 2017)
Central to this paper is the Islamic perspective of transportation planning and development. A pro-active effort consolidating major Quranic verses and the Prophets Muhammad's Hadith pertaining to the conception, development and advancement of transportation, it is a systematically documented reference for the aspiring transportation professionals including planners, engineers and academi cians. It is, by no means, a final static panacea addressing all modern days traffic blues, nor it is a reminiscence of those of 'transportation crises' i.e. the problems of congestion, pollution and accident. Rather, it is an initiation to change our tack, finding more preventative alternatives to solving transportation issues, i.e. a non-parochial outlook advocated by Al-Quran and AsSunnah.